Mathematics Applied to Engineering, Modelling, and Social Issues - Smith, Frank T.; Dutta, Hemen; Mordeson, John N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents several aspects of research on mathematics that have significant applications in engineering, modelling and social matters, discussing a number of current and future social issues and problems in which mathematical tools can be beneficial. Each chapter enhances our understanding of the research problems in a particular an area of study and highlights the latest advances made in that area. The self-contained contributions make the results and problems discussed accessible to readers, and provides references to enable those interested to follow subsequent studies in still developing fields. Presenting real-world applications, the book is a valuable resource for graduate students, researchers and educators. It appeals to general readers curious about the practical applications of mathematics in diverse scientific areas and social problems.
On the Reynolds Equation and the Load Problem in Lubrication: Literature Review and Mathematical Modelling -- On Dynamic Interactions Between Body Motion and Fluid Motion -- Certain Aspects of Problems with Non Homogenous Reactions -- A Survey on the Melnikov Theory for Implicit Ordinary Differential Equations with Applications to RLC Circuits -- Numerical solution of space-time-fractional reaction-diffusion equations via the Caputo and Riesz Derivatives -- An Extended Langhaar's Solution for Two-dimensional Entry Micro-channel Flows with High-order Slip.
Keywords: Engineering mathematics; Engineering -- Data processing; System theory; Control theory; Mathematics; Social sciences; Mathematical and Computational Engineering Applications; Systems Theory, Control; Mathematics in the Humanities and Social Sciences